Are You Happy While You Work?. (12th January 2016) - Bryson, Alex; MacKerron, George
Abstract : Using a new data source permitting individuals to record their well‐being via a smartphone, we explore within‐person variance in individuals' well‐being measured momentarily at random points in time. We find paid work is ranked lower than any of the other 39 activities individuals can report engaging in, with the exception of being sick in bed. Precisely how unhappy one is while working varies significantly with where you work; whether you are combining work with other activities; whether you are alone or with others; and the time of day or night you are working.